Non-Heart-Beating Organ Transplantation: Medical and Ethical Issues in Procurement - Institute of Medicine (The National Academies Press, 1997)
Non-heart-beating donors (individuals whose deaths are determined by cessation of heart and respiratory function rather than loss of whole brain function) could potentially be of major importance in reducing the gap between the demand for and available supply of organs for transplantation. Prompted by questions concerning the medical management of such donors—specifically, whether interventions undertaken to enhance the supply and quality of potentially transplantable organs (i.e. the use of anticoagulants and vasodilators) were in the best interests of the donor patient—the U.S. Department of Health and Human Services asked the Institute of Medicine to examine from scientific and ethical points of view "alternative medical approaches that can be used to maximize the availability of organs from [a] donor [in an end-of-life situation] without violating prevailing ethical norms...." This book examines transplantation supply and demand, historical and modern conceptions of non-heart-beating donors, and organ procurement organizations and transplant program policies, and contains recommendations concerning the principles and ethical issues surrounding the topic.
Keywords: Health and Medicine

The Whole Truth About Contraception: A Guide to Safe and Effective Choices - Beverly Winikoff; Suzanne Wymelenberg (The National Academies Press, 1997)
What birth control method is most reliable? Can contraceptives protect me from AIDS? How can I choose the method that's best for me? Finding the answers to these and other questions about birth control can be tough. On the one hand, today's sexually active person has many contraceptive options. On the other hand, each option has pluses and minuses that must be weighed. For teenagers especially, asking questions about birth control can be awkward and difficult. Yet teenagers may be in greatest need of the facts. While there is no "right" method for everyone, The Whole Truth About Contraception is the right book for anyone making decisions about contraception—men and women, from teenagers to middle-agers. It illustrates male and female anatomy and explains how conception occurs. The book carefully describes the birth control methods available today: barrier (such as condoms and diaphragms), hormonal (the Pill and Norplant), intrauterine devices, surgical sterilization, and other approaches such as the "rhythm" method and breastfeeding as a contraceptive. For each method the authors discuss how well it prevents pregnancy, its potential effects on the user's health, and common problems. Illustrated "how to" sections are provided, and the authors comment on how each method typically affects sexual experience. The book also discusses how birth control products can be obtained and their cost. Precautions, tips on usage, and other features throughout the book will help each reader decide what type of contraception is best for his or her age, personal preferences, and situation in life. The Whole Truth About Contraception gives up-to-date information on new products, such as the female condom and the nonlatex male condom. The book provides details about contraception and sexually transmitted diseases, with an emphasis on AIDS. Also offered is an expanded discussion of "emergency" contraception, designed for use after unprotected sex. The book includes a full and factual discussion of abortion. Contraception may be the most important and deeply personal choice anyone has to make. This book provides the straight facts that will make the decision easier—and the results better for everyone.
Keywords: Health and Medicine

Dispelling the Myths About Addiction: Strategies to Increase Understanding and Strengthen Research - Institute of Medicine (The National Academies Press, 1997)
Every year about half a million men, women, and children in the United States die from the effects of using nicotine, alcohol, and illegal drugs: one of every four American deaths. Yet research to solve this terrible problem is often perceived as less important than other types of biomedical investigation. Focusing on four major classes of drugs with the greatest social and economic impact—nicotine, alcohol, opioids, and stimulants—Dispelling the Myths About Addiction examines what is known about addiction and what is needed to develop a talented cadre of investigators and to educate the public about addiction research. The committee explores these areas: Economic costs of addiction. What has been learned about addiction from research into basic neurobiology and the brain, psychosocial and behavioral factors, and epidemiology. Education and training of researchers and the research infrastructure. Public perceptions and their impact on public policy in this field. This volume outlines the challenges and opportunities in addiction research today and makes recommendations to educators, treatment professionals, public and private institutions, and others for how to build support for addiction research and treatment.
Keywords: Health and Medicine

Pharmacokinetics and Drug Interactions in the Elderly and Special Issues in Elderly African-American Populations: Workshop Summary - Institute of Medicine (The National Academies Press, 1997)
Reports in the popular press about the increasing longevity of Americans and the aging of the baby boom generation are constant reminders that the American population is becoming older. Consequently, an issue of growing medical, health policy, and social concern is the appropriate and rational use of medications by the elderly. Although becoming older does not necessarily correlate with increasing illness, aging is associated with anatomical and physiological changes that affect how medications are metabolized by the body. Furthermore, aging is often related to an increased frequency of chronic illness (often combined with multiple health problems) and an increased use of medications. Thus, a better understanding of the absorption, distribution, metabolism, and excretion of drugs; of the physiologic responses to those medications; as well as of the interactions among multiple medications is crucial for improving the health of older people.
Keywords: Health and Medicine

Enabling America: Assessing the Role of Rehabilitation Science and Engineering - Institute of Medicine (The National Academies Press, 1997)
The most recent high-profile advocate for Americans with disabilities, actor Christopher Reeve, has highlighted for the public the economic and social costs of disability and the importance of rehabilitation. Enabling America is a major analysis of the field of rehabilitation science and engineering. The book explains how to achieve recognition for this evolving field of study, how to set priorities, and how to improve the organization and administration of the numerous federal research programs in this area. The committee introduces the "enabling-disability process" model, which enhances the concepts of disability and rehabilitation, and reviews what is known and what research priorities are emerging in the areas of: Pathology and impairment, including differences between children and adults. Functional limitations—in a person's ability to eat or walk, for example. Disability as the interaction between a person's pathologies, impairments, and functional limitations and the surrounding physical and social environments. This landmark volume will be of special interest to anyone involved in rehabilitation science and engineering: federal policymakers, rehabilitation practitioners and administrators, researchers, and advocates for persons with disabilities.
Keywords: Health and Medicine

Emerging Technologies for Nutrition Research: Potential for Assessing Military Performance Capability - Institute of Medicine (The National Academies Press, 1997)
The latest of a series of publications based on workshops sponsored by the Committee on Military Nutrition Research, this book's focus on emerging technologies for nutrition research arose from a concern among scientists at the U.S. Army Research Institute of Environmental Medicine that traditional nutrition research, using standard techniques, centered more on complex issues of the maintenance or enhancement of performance, and might not be sufficiently substantive either to measure changes in performance or to predict the effects on performance of stresses soldiers commonly experience in operational environments. The committee's task was to identify and evaluate new technologies to determine whether they could help resolve important issues in military nutrition research. The book contains the committee's summary and recommendations as well as individually authored chapters based on presentations at a 1995 workshop. Other chapters cover techniques of body composition assessment, tracer techniques for the study of metabolism, ambulatory techniques for the determination of energy expenditure, molecular and cellular approaches to nutrition, the assessment of immune function, and functional and behavioral measures of nutritional status.
Keywords: Food and Nutrition; Health and Medicine

Reproductive Health in Developing Countries: Expanding Dimensions, Building Solutions - National Research Council (The National Academies Press, 1997)
Sexually transmitted diseases, unintended pregnancies, infertility, and other reproductive problems are a growing concern around the world, especially in developing countries. Reproductive Health in Developing Countries describes the magnitude of these problems and what is known about the effectiveness of interventions in the following areas: Infection-free sex. Immediate priorities for combating sexually transmitted and reproductive tract diseases are identified. Intended pregnancies and births. The panel reports on the state of family planning and ways to provide services. Healthy pregnancy and delivery. The book explores the myths and substantive socio-economic problems that underlie maternal deaths. Healthy sexuality. Such issues as sexual violence and the practice of female genital mutilation are discussed in terms of the cultural contexts in which they occur. Addressing the design and delivery of reproductive health services, this volume presents lessons learned from past programs and offers principles for deciding how to spend limited available funds. Reproductive Health in Developing Countries will be of special interest to policymakers, health care professionals, and researchers working on reproductive issues in the developing world.
Keywords: Health and Medicine

Managing Managed Care: Quality Improvement in Behavioral Health - Institute of Medicine (The National Academies Press, 1997)
Managed care has produced dramatic changes in the treatment of mental health and substance abuse problems, known as behavioral health. Managing Managed Care offers an urgently needed assessment of managed care for behavioral health and a framework for purchasing, delivering, and ensuring the quality of behavioral health care. It presents the first objective analysis of the powerful multimillion-dollar accreditation industry and the key accrediting organizations. Managing Managed Care draws evidence-based conclusions about the effectiveness of behavioral health treatments and makes recommendations that address consumer protections, quality improvements, structure and financing, roles of public and private participants, inclusion of special populations, and ethical issues. The volume discusses trends in managed behavioral health care, highlighting the emerging role of the purchaser. The committee explores problems of overlap and fragmentation in the delivery of behavioral health care and discusses the issue of access, a special concern when private systems are restricted and public systems overburdened. Highly applicable to the larger health care system, this volume will be of particular interest to all stakeholders in behavioral health—federal and state policymakers, public and private purchasers, health care providers and administrators, consumers and consumer advocates, accrediting organizations, and health services researchers.
Keywords: Health and Medicine

Improving Health in the Community: A Role for Performance Monitoring - Institute of Medicine (The National Academies Press, 1997)
How do communities protect and improve the health of their populations? Health care is part of the answer but so are environmental protections, social and educational services, adequate nutrition, and a host of other activities. With concern over funding constraints, making sure such activities are efficient and effective is becoming a high priority. Improving Health in the Community explains how population-based performance monitoring programs can help communities point their efforts in the right direction. Within a broad definition of community health, the committee addresses factors surrounding the implementation of performance monitoring and explores the "why" and "how to" of establishing mechanisms to monitor the performance of those who can influence community health. The book offers a policy framework, applies a multidimensional model of the determinants of health, and provides sets of prototype performance indicators for specific health issues. Improving Health in the Community presents an attainable vision of a process that can achieve community-wide health benefits.
Keywords: Health and Medicine

Approaching Death: Improving Care at the End of Life - Institute of Medicine (The National Academies Press, 1997)
When the end of life makes its inevitable appearance, people should be able to expect reliable, humane, and effective caregiving. Yet too many dying people suffer unnecessarily. While an "overtreated" dying is feared, untreated pain or emotional abandonment are equally frightening. Approaching Death reflects a wide-ranging effort to understand what we know about care at the end of life, what we have yet to learn, and what we know but do not adequately apply. It seeks to build understanding of what constitutes good care for the dying and offers recommendations to decisionmakers that address specific barriers to achieving good care. This volume offers a profile of when, where, and how Americans die. It examines the dimensions of caring at the end of life: Determining diagnosis and prognosis and communicating these to patient and family. Establishing clinical and personal goals. Matching physical, psychological, spiritual, and practical care strategies to the patient's values and circumstances. Approaching Death considers the dying experience in hospitals, nursing homes, and other settings and the role of interdisciplinary teams and managed care. It offers perspectives on quality measurement and improvement, the role of practice guidelines, cost concerns, and legal issues such as assisted suicide. The book proposes how health professionals can become better prepared to care well for those who are dying and to understand that these are not patients for whom "nothing can be done."
Keywords: Health and Medicine

A Review of the Department of Defense's Program for Breast Cancer Research - Institute of Medicine (The National Academies Press, 1997)
According to current statistical data, one in eight women will be diagnosed with breast cancer. The five-year survival rate for breast cancer patients has improved in recent years, but the overall mortality rates have changed little. In 1993 Congress allocated $210 million for breast cancer research as part of the Department of Defense budget. An Institute of Medicine (IOM) committee was convened at that time to advise the U.S. Army Medical Research and Development Command on strategies for managing a breast cancer research program. This book evaluates the program's management and achievements to date. Although it is too early to evaluate the program in terms of breakthrough results and new insights produced by the funded projects or investigators, this book documents the process used to select research proposals for funding and analyzes the portfolio of funded projects in terms of their responsiveness to the recommendations and fundamental questions articulated in the 1993 IOM report.
Keywords: Health and Medicine

Characterizing Exposure of Veterans to Agent Orange and Other Herbicides Used in Vietnam: Scientific Considerations Regarding a Request for Proposals for Research - Institute of Medicine (The National Academies Press, 1997)
Keywords: Health and Medicine

Adequacy of the Comprehensive Clinical Evaluation Program: A Focused Assessment - Institute of Medicine (The National Academies Press, 1997)
Keywords: Health and Medicine

Managing Managed Care: Quality Improvement in Behavioral Health: Summary - Institute of Medicine (The National Academies Press, 1997)
Keywords: Health and Medicine

The Hidden Epidemic: Confronting Sexually Transmitted Diseases - Institute of Medicine (The National Academies Press, 1997)
The United States has the dubious distinction of leading the industrialized world in overall rates of sexually transmitted diseases (STDs), with 12 million new cases annually. About 3 million teenagers contract an STD each year, and many will have long-term health problems as a result. Women and adolescents are particularly vulnerable to these diseases and their health consequences. In addition, STDs increase the risk of HIV transmission. The Hidden Epidemic examines the scope of sexually transmitted infections in the United States and provides a critical assessment of the nation's response to this public health crisis. The book identifies the components of an effective national STD prevention and control strategy and provides direction for an appropriate response to the epidemic. Recommendations for improving public awareness and education, reaching women and adolescents, integrating public health programs, training health care professionals, modifying messages from the mass media, and supporting future research are included. The book documents the epidemiological dimensions and the economic and social costs of STDs, describing them as "a secret epidemic" with tremendous consequences. The committee frankly discusses the confusing and often hypocritical nature of how Americans deal with issues regarding sexuality—the conflicting messages conveyed in the mass media, the reluctance to promote condom use, the controversy over sex education for teenagers, and the issue of personal blame. The Hidden Epidemic identifies key elements of effective, culturally appropriate programs to promote healthy behavior by adolescents and adults. It examines the problem of fragmentation in STD services and provides examples of communities that have formed partnerships between stakeholders to develop integrated approaches. The committee's recommendations provide a practical foundation on which to build an integrated national program to help young people and adults develop habits of healthy sexuality. The Hidden Epidemic was written for both health care professionals and people without a medical background and will be indispensable to anyone concerned about preventing and controlling STDs.
Keywords: Health and Medicine

In Her Own Right: The Institute of Medicine's Guide to Women's Health Issues - Institute of Medicine (The National Academies Press, 1997)
Right to life. Right to choice. Masectomy, lumpectomy. Vitamin therapy, hormone therapy, aromatherapy. Tabloids, op-eds, Phil, Sally, Oprah. Yesterday, women confided in their doctors about health problems and received private, albeit sometimes paternalistic, attention. Today, women's health issues are headline material. Topics that once raised a blush now raise a blare of conflicting medical news and political advocacy. Women welcome the new recognition of their health concerns. Now women are less often treated, as the old saw goes, as "a uterus with a person attached." At the same time, they need help in sorting through the flood of reports on scientific studies, claims of success for new treatments, and just plain myths. The Institute of Medicine (IOM) has responded to this need with In Her Own Right. Throughout its 25-year history, the IOM has provided authoritative views on fast-moving developments in medicine—bringing accuracy, objectivity, and balance to the hottest controversies. Talented science writer Beryl Lieff Benderly synthesizes this expertise into a readable overview of women's health. Why do women live longer than men? Why do more women than men suffer vertebral fractures? Benderly highlights what we know about the health differences between men and women and the mysteries that remain to be solved. With a frank, conversational approach, Benderly examines women's health across the life span: Issues of female childhood, adolescence, and sexual maturity, including smoking, eating behavior, teen pregnancy, and more. The host of issues surrounding the reproductive years; contraception, infertility, abortion, pregnancy and birth, AIDS, and mental health. Postmenopausal life and issues of aging, as health choices made decades earlier come home to roost. Benderly addresses women's experience with the nation's health care establishment and the controversy over the lack of female representation in the world of scientific research. Much more than a how-to guide, In Her Own Right translates the finest scholarship on topics of women's health into terms that will help any woman ask the right questions and make the right choices. Covering the spectrum from traditional beliefs to cutting-edge research, this book presents the personal insights of leading investigators, along with clear explanations of breakthrough studies written in plain English.
Keywords: Health and Medicine

Halcion: An Independent Assessment of Safety and Efficacy Data - Institute of Medicine (The National Academies Press, 1997)
Regulatory agencies within the United States and the United Kingdom, among several other countries, have reviewed extensively the safety and efficacy of Halcion (triazolam)—a once commonly used hypnotic drug. Concerns began to emerge about the safety of Halcion when a Dutch physician reported a possible link between it and a syndrome that included such effects as depression, amnesia, hallucinations, and increased anxiety. In addition, in 1991 its manufacturer, Upjohn, noted that "errors had been identified in a report of one of the clinical studies included in the original" application for approval. Since then, the drug has been removed from the market in several countries, whereas in the United States and Canada, the drug's labeling has been modified to reduce the recommended dose and duration of treatment and to heighten awareness of possible side effects. Yet different data and analyses have resulted in conflicting messages that are difficult to reconcile and interpret. In response to a request from the Food and Drug Administration to resolve these controversial issues related to the safety and efficacy of Halcion, this IOM book assesses the adequacy of the drug's clinical trials; the quality and quantity of data on adverse reactions; overall confidence in the data on effectiveness, adverse events, and side effects at different doses; and whether additional studies are needed.
Keywords: Health and Medicine

The Lessons and The Legacy of the Pew Health Policy Program - Institute of Medicine (The National Academies Press, 1997)
Keywords: Health and Medicine

Veterans and Agent Orange: Update 1996: Summary and Research Highlights - Institute of Medicine (The National Academies Press, 1997)
Keywords: Health and Medicine

Vaccine Safety Forum: Summaries of Two Workshops - Institute of Medicine (The National Academies Press, 1997)
On November 6, 1995, the Institute of Medicine's Vaccine Safety Forum convened a workshop on detecting and responding to adverse events following vaccination. Workshop speakers and participants discussed the difficulties in detecting adverse events, current adverse events detection and response methods and procedures, suggestions for improving the means of detecting and responding to adverse events following vaccination, and future areas of research. This document represents a summary of that workshop.
Keywords: Health and Medicine